Self-Insertion of Urethral Foreign Body: Performing Azayem Procedure for Metal Forceps Removal from Urethra - Perdana, Noor Riza; Shalatin, Herdiko; Yulizar, Deddy Rasyidan; Sutapa, Hendra (Open Access Macedonian Journal of Medical Sciences, 2022)
Self-inserted male urethral foreign bodies are urological emergencies that we as urologists might have to deal with in the future. The number of case self-inserted foreign bodies have been increasing respectively the last decade especially in male patients. We report a case of a 27-year-old male with a self-inserted foreign body (forceps) into the urethra and the evacuation using the Azayem procedure. The presentation consists of the clinical features of this patient, including medical history, signs, and symptoms, imaging examinations were recorded. After diagnosis and endoscopic preparations, the procedure to evacuate a self-inserted foreign body was performed. We performed the Azayem procedure on the patient who was complaining of dysuria, hematuria, pyuria, and palpable urethral foreign body caused by forceps that was self-inserted 11 days before admission. Azayem procedure is a simple endoscopic technique for removing the metal hair removal forceps from the urethra. We then treated the urethral injury and the infection as the most concerning complications. Psychology follow-up by psychiatrist, urethrography and International Prostate Symptom Score evaluation was taken as the follow-up post-procedure. A self-inserted foreign body is a rare case and life-threatening related to urosepsis caused by the late intervention. The variety of foreign bodies inserted into the urethra includes forceps. Azayem procedure is an effective approach to evacuate forceps as the urethral foreign body because this endoscopic procedure is relatively simple to perform and has a minimal procedural complication.